STUDENTS’ SELF-REGULATED LEARNING IN ENGLISH OF SECOND GRADE AT SMAN ISLAM TERPADU SYECH WALID THAIB SALEH INDRAGIRI TELUK SUNGKA - Siti Raudhah; Melda Yeni; Sri Erma Purwanti (Program Studi Pendidikan Bahasa Inggris, 2022)
This study aims to find the students' self-regulated learning in English of second grade at SMAN Islam Terpadu Syech Walid Thaib Shaleh Indragiri Teluk Sungka. This type of research is descriptive quantitative. To find the purpose of this study, the researcher used the method of collecting data through a questionnaire. After gathering the data, the researcher found that the results of this study of self-regulated learning showed that regulated learning with 35 students as respondents with an average score of 141.1 was included in the